2021
DOI: 10.1101/2021.02.18.431867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strongyloides RNA-seq Browser: a web-based software platform for on-demand bioinformatics analyses of Strongyloides species

Abstract: Soil-transmitted gastrointestinal parasitic nematodes infect approximately 1 billion people worldwide, predominantly in low-resource communities. Skin-penetrating gastrointestinal nematodes in the genus Strongyloides are emerging as model systems for mechanistic studies of soil-transmitted helminths due to the growing availability of functional genomics tools for these species. To facilitate future genomics studies of Strongyloides species, we have designed a web-based application, the Strongyloides RNA-seq Br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…B. Behavioral responses of distinct life stages of S. stercoralis to CO2 in a chemotaxis assay. See also [29][30][31]. Each data point represents a single biological replicate; lines indicate medians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Behavioral responses of distinct life stages of S. stercoralis to CO2 in a chemotaxis assay. See also [29][30][31]. Each data point represents a single biological replicate; lines indicate medians.…”
Section: Discussionmentioning
confidence: 99%
“…The Ss-gcy-9 gene encodes a protein with a domain structure resembling that of other rGC proteins -it includes an extracellular ligand-binding domain, a transmembrane domain, an intracellular kinase domain, and a guanylate cyclase domain (Figure S2A-B). To better characterize the Ss-gcy-9 gene, we first analyzed its expression levels across life stages using the available life-stage-specific transcriptomic dataset for S. stercoralis [29][30][31]. We found that this gene is expressed at low levels in post-parasitic L1/L2 larvae and free-living adults but is highly expressed in iL3s (Figure 2A).…”
Section: The Receptor Guanylate Cyclase Gcy-9 Mediates Behavioral And...mentioning
confidence: 99%
“…This raises questions about how clinical steroids and other medication can affect parasite development and survival in endemic strongyloidiasis. As we continue to generate and collate Strongyloides transcriptome data, data repositories and software such as the Strongyloides RNA-seq Browser [76] will be useful in combining existing data from Strongyloides species and will facilitate easier comparative gene expression and enrichment analyses.…”
Section: S S T E R C O R a L I S S R A T T I S V E N E Z U E L E N...mentioning
confidence: 99%
“…This is owing, in part, to the historical lack of functional genomics techniques adapted for use in these species. However, recent efforts have significantly advanced the number of functional genomics pipelines and bioinformatics tools in Strongyloides species, including protocols for transgenesis, CRISPR/Cas9-mediated mutagenesis, RNA interference (RNAi), chemogenetic neuronal silencing, fluorescent biosensor imaging and on-demand analysis of gene expression and codon usage [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Technical advances in the functional Strongyloides toolkit have been enabled by publicly available descriptive genome biodata, including high-quality reference genomes, RNA-sequencing (RNA-Seq) datasets and automated genome annotations that identify predicted gene models [9,10,[13][14][15]. Genome annotations are a cornerstone of high-throughput and targeted genomics studies: they serve as a scaffold for alignment and quantification of RNA-Seq data; they also enable researchers to more easily identify putative promoter regions for transcriptional reporters, exon sequences for RNAi, target sites for CRISPR/Cas9-mediated mutagenesis and predicted protein sequences for comparative genomics and ectopic expression studies [5,6,8,11,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%